Understanding Profiles of Preservice Teachers With Different Levels of Commitment to Teaching in Urban Schools. (July 2014) - Aragon, Antonette; Culpepper, Steven A.; McKee, Malaika W.; Perkins, Mark
Understanding the beliefs of preservice teachers is an important area to investigate in the teacher education process. This article examines the relationship between preservice teachers' beliefs pertaining to diversity and urban schooling and how these inclinations contribute to a commitment to teaching urban students. Canonical correlation analysis was used to identify profiles of preservice teachers who exhibited varying degrees of interest to teach in urban schools. The statistical analysis provides a range of positive and negative attitudinal inclinations toward urban teaching. It is important to examine preservice teacher beliefs to benefit students in urban schools especially in light of prevailing teacher attrition.